Fast and easy preoperative estimation of cancellous bone mineral density in patients with proximal femur fractures - Erhart, S.; Zegg, M.; Kralinger, F.; Kammerlander, C.; Roth, Tobias (Archives of orthopaedic and trauma surgery, 2015)
Introduction Postoperative complications after hip fractures in osteoporotic bone such as implant cutout can be reduced by the use of specially designed implants or additional cement augmentation. It is not yet clear at which degree of osteoporosis, patients will profit from implant augmentation or specially designed implants for geriatric patients. As the surgeon ideally should obtain information on local bone quality at the site of implant anchorage already preoperatively, the aim of the study was to develop an easily applicable radiographic method to estimate bone quality in those patients. Materials and methods 75 patients with unilateral hip fracture were included. Preoperatively, a CT scan with a calibration device was conducted. Postoperatively, DXA scans were performed. The proposed method measures local cancellous bone mineral density in the contralateral and uninjured femoral head. As a control, 15 young and healthy non-osteoporotic subjects were included. Inter- and intraobserver reliability was investigated for a subgroup of 20 patients. Results Study group patients had a mean BMD measured by CT scans of 194.2 mg/cm 3 (SD 40.4). There was a statistically significant correlation with data from DXA scans ( r = 0.706, p < 0.001). The control group was significantly younger and showed a significantly higher BMD when compared to the study group ( p < 0.001). Reliability evaluation showed no statistically significant difference in inter- and intraobserver measurements. Interclass correlation proved to be very high. Conclusion The proposed method is an easily applicable, reliable and useful tool to estimate bone quality preoperatively using the contralateral hip as a reference. Obtained data may facilitate the decision-making towards the use of further therapeutic measures to improve implant anchorage in osteoporotic bone such as bone cement augmentation. Thus, our method allows for a more individualized surgical treatment of hip fracture patients adapted to the estimated cancellous bone quality of the patient.